Evaluation of ecological risk based on the sediment and water quality in Klang Strait, Malaysia / Seyedeh Belin Tavakoly Sany - Tavakoly Sany, Seyedeh Belin (2012)
Sediment and water monitoring was performed from Nov. 2009 to Oct. 2010 to assess and evaluate the spatial and temporal distribution of physical and chemical parameters and biological variables such as PAHs, trace metals (Hg, Cd, Pb, Cu, Mn, Zn, Cr, Ni, V, and Fe), the structure of the benthic community in the sediment, nutrients and chlorophyll a in the water. Sediment and water samples were collected from 22 stations, which covered three coastal ports (North Port, West Port and South Port) and a control point. The primary objectives of this study were to evaluate the sources of pollutants and each pollutant’s distribution, concentration and contamination degree, as well as to assess the biological response to these stressors based on the ecological risk. Significant variations were found in the distribution and concentrations of all heavy metals and PAHs. The spatial and temporal scales of these variations were related to the several sources contributing to the contamination load in the Klang Strait and to seasonal fluctuations, respectively. The highest concentrations of all metals (except for Mn) were recorded at South Port at stations 16 and 17 parallel to the mouth of the Klang River and at station 13 around the container terminal in the West Port, whereas the lowest concentrations were recorded at the control point. Enrichment factor (EF) index also indicated that all metal concentrations except for Fe were influenced by anthropogenic effects. Similarly, the total organic carbon and fine particle size had significant correlations with most metals (Al, Cd, Cu, Fe, Ni, V and Zn). Thus, both natural processes and human activities contributed to the load of these pollutions in the Klang Strait. The PCA analysis is concordant with the pair isomer ratio of PAHs, which revealed that the anthropogenic sources of PAHs were a mixture of pyrogenic and petrogenic sources at all stations except for stations 4, 14 and 21, where combustion was the more frequent cause. Source analysis revealed that PAHs are primarily derived from liquid fossil fuels related to the use of vehicles, crude oil and coal (petroleum combustion sources), and a minor amount of PAHs may be related to the direct discharge of petroleum and land-based runoff. Results revealed that most of the sediment samples are in a pristine state with respect to PAHs and metal contamination except for Cd, As, Hg and Pb. Surface sediment in the Klang Strait are moderately polluted by Hg, Pb and As, and only Cd was estimated to have a high level of contamination. Furthermore, risk analysis showed that living organisms in the strait have a high risk of Cd and Hg exposure and only a low risk of overexposure to the rest of the investigated metals and PAHs at all stations. Regarding the risk index classification, only sediments from stations 16 and 17 (mouth of the Klang River) can be considered to represent a high ecological risk. Other stations were categorized as representing slight to moderate risk, and adverse effects were rarely recorded at the control station, which usually showed normal responses. In addition, the level of response of benthic communities to pollutants in the sediment was completely homogeneous with the risk level in most of the stations. In the case of water-quality assessment, multi-metric indices and operational indicator have been proposed to classify trophic level at different sites. The trophic level of Klang Strait coastal water ranges from eutrophic to hypertrophic. Chl-a concentration was used to estimate the biological response of phytoplankton biomass and indicated eutrophic conditions in the Klang Strait and mesotrophic conditions at the control site. During the study period, no harmful algal bloom (secondary symptom) occurred, which may be related to hydrodynamic turbulence and water exchange, which prevent the development of eutrophic conditions in the Klang Strait. Keywords: Ecological risk, Heavy metal, Polyaromatic hydrocarbons (PAHs), Nutrients, Benthic organisms, Chlorophill a, Klang Strait, Malaysia